2020
DOI: 10.31348/2020/16
|View full text |Cite
|
Sign up to set email alerts
|

Aflibercept for Vascularised Serous Pigment Epithelial Detachment: One-Year Anatomical and Functional Results

Abstract: Purpose: To assess the effect of intravitreal aflibercept on pigment epithelial detachment (PED) secondary to occult choroidal neovascularization (CNV) in treatment-naive patients. Patients and methods: Retrospective analysis of thirty-six patients (thirty-eight eyes) with mean age 77 (SD ± 7), who were treated with aflibercept 2.0 mg (Eylea, Bayer) at the Department of Ophthalmology of 1st Faculty of Medicine of the Charles University and the Military University Hospital Prague. All patients were treated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Another important consideration in the decision to transition to IVA is the presence of a vascularized PED which can be a treatment challenge in eyes with eAMD. Multiple studies have demonstrated significant benefits to the use of IVA over other anti-VEGF agents with flattening of the vascularized PED and improved visual acuity results [ 65 , 66 , 67 ]. Furthermore, multiple investigators have demonstrated a beneficial anatomic response in such eyes resistant to IVB or IVR associated with stable visual acuity outcomes [ 68 , 69 , 70 , 71 ].…”
Section: Exudative Age-related Macular Degenerationmentioning
confidence: 99%
“…Another important consideration in the decision to transition to IVA is the presence of a vascularized PED which can be a treatment challenge in eyes with eAMD. Multiple studies have demonstrated significant benefits to the use of IVA over other anti-VEGF agents with flattening of the vascularized PED and improved visual acuity results [ 65 , 66 , 67 ]. Furthermore, multiple investigators have demonstrated a beneficial anatomic response in such eyes resistant to IVB or IVR associated with stable visual acuity outcomes [ 68 , 69 , 70 , 71 ].…”
Section: Exudative Age-related Macular Degenerationmentioning
confidence: 99%